BUTYLTIN RESIDUES IN SEDIMENTS FROM THE EASTERN GULF OF THAILAND - Praditsup, Nichaya; Wattayakorn, Gullaya (Marine Research in Indonesia, 2014)
Concentrations of monobutyltin (MBT), dibutyltin (DBT) and tributyltin (TBT) compounds were analyzedÃÂ in surface sediment samples collected from twelve stations along the Eastern Gulf of Thailand. The total butyltinÃÂ (Ã¢ËâBTs) concentrations ranged between <1 and 109.7 ng gÃÂ (dry weight). The overall concentration ranges foundÃÂ in the sediments were from <1 to 79.81 ng g-1ÃÂ for MBT, from <1 to 9.5 ng gÃÂ -1ÃÂ for DBT, and from <1 to 29.8 ng g-1 for TBT, on a dry weight basis. MBT generally prevailed in most of the samples, suggesting the occurrence of old inputs of butyltin compounds in the area. Butyltin compounds were also measured in Nassarius sp., where Ã¢ËâBTs concentrations were found to range between <1 and 238 ng g-1 (wet weight). The level of butyltin compounds in gastropod tissue samples tended to be related to that of the sediments and percentage of imposex incidence.